State Papers Foreign, Barbary States (Tunis) 1736-1769 (Records of the Public Record Office., 1970)
Correspondence and papers of the Secretary of State concerning the Barbary States. The records relate to Algiers, 1595-1780; Morocco, 1577-1774; Tripoli, 1590-1780 and Tunis, 1622-1780. The records are mainly in-letters (with some extracts) to the Secretary of State from the English or British consuls, eg in Algiers, Salé, Tripoli, Tunis, or Tetuan (Tétouan), together with a number of draft replies. Included are original letters from heads of state (including the Emperor of Morocco) and their ministers, and certain foreign ambassadors. Petitions to the Secretary of State, and several royal warrants and instructions to the consuls or agents acting for the government may also be found.